Evaluation of Science Teachers’ Knowledge towards Mumps Disease in Primary Schools (Medico Legal Update, 2020)
A descriptive study has been used the evaluating science teachers’ knowledge towards mumps diseasein primary schools. A probability (simple random sample) the sample consisted of 60 science teachersfrom 60 primary schools in Holy Kerbala city, during the period of January 2018 to the end of June 2019.The questionnaire involved two-part: the first, demographic data of teachers such as age, gender, andspecialization, level of education, years of employment, participation in training course or workshop towardcommunicable diseases and second part, concerning teachers’ knowledge about mumps in primary schoolswere comprised of (36) items divided to (6) items related to knowledge about anatomy and physiological ofsalivary glands, general knowledge about mumps (5) items, knowledge about signs and symptoms of mumpsdisease (7) items, knowledge about diagnosis and complications of mumps disease (6) items, knowledgeabout mode of transmission for mumps infection (6) items, knowledge about prevention and treatmentof mumps disease. The data was collected by a questionnaire which consisted of two parts, the first partconsists socio-demographic data, second part was about the knowledge of mumps disease which consistof (36) items scale of knowledge about mumps disease. In the present study, data were analyzed throughthe use of statistical package for social sciences (SPSS), version 24. The finding of the study indicated thatmost of the teachers who participated in the study were female, most of them graduated from institutes andthey have an extremely low level of knowledge toward mumps ranges between poor and fair. The studyrecommends encouraging teachers’ participation in the health education program, especially programs thatdeal with communicable diseases because the risk of spread these diseases among the school community.